Portability of pension, health, and other social benefits: Facts, concepts, and issues - Robert Holzmann; Johannes Koettl (Center for Economic Studies and ifo Institute (CESifo), 2012)
Portability of social benefits across professions and countries is an increasing concern for individuals and policy makers. Lacking or incomplete transfers of acquired social rights are feared to negatively impact individual labor market decisions as well as capacity to address social risks with consequences for economic and social outcomes. The paper gives a fresh and provocative look on the international perspective of the topic that has so far been dominated by social policy lawyers working within the framework of bilateral agreements; the input by economists has been very limited. It offers an analytical framework for portability analysis that suggests separating the risk pooling, (implicit or actual) pre-funding, and redistributive elements in the benefit design, and explores the proposed alternative approach for pensions and health care benefits. This promising approach may serve both as a substitute and complement to bi- and multilateral agreements.
Keywords: D69; 330; acquired rights; labor mobility; migration; individual accounts; bi-lateral agreements